Copper‐Catalyzed Oxygenative Skeletal Rearrangement of Tetrahydro‐β‐carbolines Using H2O and O2 as Oxygen Sources - Peng, Yu‐Sheng; Wang, Wei; Shi, Jun; Wu, Wei; Song, Jun‐Rong; Pan, Wei‐Dong; Hao, Ge‐Fei; Ren, Hai (Angewandte Chemie International Edition, 2023)
Herein, we report an unprecedented skeletal rearrangement reaction of tetrahydro‐β‐carbolines enabled by copper‐catalyzed single‐electron oxidative oxygenation, in which H2O and O2 act as oxygen sources to generate a unique 2‐hydroxyl‐3‐peroxide indoline intermediate. The synthetic reactivity of 2‐hydroxyl‐3‐peroxide indoline species was demonstrated by a unique multi‐step bond cleavage and formation cascade. Using a readily available copper catalyst under open‐air conditions, highly important yet synthetically difficult spiro[pyrrolidone‐(3,1‐benzoxazine)] products were obtained in a single operation. The synthetic utility of this methodology is demonstrated by the efficient synthesis of the natural products donaxanine and chimonamidine, as well as the 3‐hydroxyl‐pyrroloindoline scaffold, in just one or two steps. An unprecedented oxygenative skeletal rearrangement reaction of tetrahydro‐β‐carbolines (THβCs) was developed under mild conditions enabled by copper‐catalyzed single‐electron transfer oxidation, in which H2O and O2 act as oxygen sources to generate a unique 2‐hydroxyl‐3‐peroxide indoline intermediate. The process involves a multistep sequence to enable the transformation of THβCs to donaxanine‐type heterocycles in an efficient manner.